Biogenic Amines: Signals Between Commensal Microbiota and Gut Physiology - Sudo, Nobuyuki (Frontiers in Endocrinology, 2019)
There is increasing interest in the interactions among the gut microbiota, gut, and brain, which is often referred to as the “microbiota-gut-brain” axis. Biogenic amines including dopamine, norepinephrine, serotonin, and histamines are all generated by commensal gut microorganisms and are suggested to play roles as signaling molecules mediating the function of the “microbiota-gut-brain” axis. In addition, such amines generated in the gut have attracted attention in terms of possible clues into the etiologies of depression, anxiety, and even psychosis. This review covers the latest research related to the potential role of microbe-derived amines such as catecholamine, serotonin, histamine, as well as other trace amines, in modulating not only gut physiology but also brain function of the host. Further attention in this field can offer not only insight into expanding the fundamental roles and impacts of the human microbiome, but also further offer new therapeutic strategies for psychological disorders based on regulating the balance of resident bacteria.